HUBUNGAN KETEBALAN LEMAK DENGAN VO2 MAX ATLET GULAT PPLP RIAU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The problem in this study is that the thickness of an athlete's fat in wrestling can inhibit the athlete's vo2 max in attacking and slamming opponents during training or competition. The purpose of this study was to determine the contribution of fat thickness to the vo2 max of Riau PPLP wrestling athletes. The population in this study was PPLP Riau wrestling athletes as many as 8 male wrestlers. The sampling technique was determined by total sampling. After the data was obtained from the results of the anthropometric test of measuring fat thickness using a skinfold caliper and beep test, the data would be analyzed by testing the normality of the data using the Liliefors test. To find out whether a data is normal or not, if Lo Max < L table then the sample comes from a normally distributed population, it can be seen that the X variable value Lomax = 0.235 and the Y variable value Lo max = 0.173. Where Ltable with a significance level of 5% = 0.258. Thus the variable X value Lo max = 0.235 < Ltable = 0.258 and the variable Y value Lo max = 0.173 < Ltable = 0.258. Based on the correlation test, it can be concluded that there is a significant relationship between the relationship between fat thickness and vo2 max where the value of rcount = 0.976> rtable = 0.707. therefore Ha is accepted and Ho is rejected. This means that there is a relationship between fat thickness and Vo2 Max endurance of PPLP Riau Wrestling Athletes, where the provision is that there is a correlation between one variable and other variables determined from r count>r table.Key Words: Complete Nutrition Guide, Physical Condition Development,Wrestling Sports Module